1993
DOI: 10.1063/1.109259
|View full text |Cite
|
Sign up to set email alerts
|

Selective area oxidation of silicon with a scanning force microscope

Abstract: The use of a scanning force microscope with a metallized tip to do selective area oxidation of silicon is demonstrated. Sub-100 nm lines have been achieved. Removal of the oxide lines with buffered hydrofluoric acid reveals trenches in the silicon consistent with silicon consumption in SiO2 formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
127
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 231 publications
(137 citation statements)
references
References 11 publications
1
127
0
2
Order By: Relevance
“…In 1993 it was demonstrated that local oxidation experiments could be performed with an atomic force microscope. 16 This Fig. 1 Scheme of some common mechanisms to modify surfaces with scanning probe nanolithographies.…”
Section: Local Oxidation Nanolithographymentioning
confidence: 99%
See 1 more Smart Citation
“…In 1993 it was demonstrated that local oxidation experiments could be performed with an atomic force microscope. 16 This Fig. 1 Scheme of some common mechanisms to modify surfaces with scanning probe nanolithographies.…”
Section: Local Oxidation Nanolithographymentioning
confidence: 99%
“…They serve as a good model to illustrate some of the fundamental aspects involved in the local oxidation process. [16][17][18][19] Voltage pulses are applied to generate an oxide dot. The dot size depends linearly on voltage strength but the dot height shows a power law dependence of the type…”
Section: Local Oxidation Nanolithographymentioning
confidence: 99%
“…The oxide is used as an etch mask so that two-dimensional patterns can be transferred into the silicon. For lithographic purposes the process has been demonstrated using a scanning tunneling microscope ͑STM͒, 1-5 an atomic force microscope ͑AFM͒, 6,7 and electron beam lithography. 4,8 More recently, optically induced hydrogen desorption was reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Recently this field has experienced a renovated interest. For one side, several results have contributed to an increased understanding of the oxidation mechanism in silicon surfaces 15,16 and its kinetics.…”
Section: Introductionmentioning
confidence: 99%